2016
DOI: 10.3141/2576-04
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Indicators for Fatigue Cracking in Hot-Mix Asphalt Pavements Using Viscoelastic Continuum Damage Principles

Abstract: A critical distress in asphalt concrete pavements is fatigue cracking, which results in decreased ride quality and fuel economy, and provides an avenue for water intrusion, which causes a pavement system to deteriorate rapidly. Given the poor state of the infrastructure network, changes are needed in the current mixture design process to promote innovation and alternative approaches to production. This study addressed this need by pursuing the following objectives: ( a) relate mixture stiffness, fatigue, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The research has also demonstrated that the stiffness of non-asphalt layers and the layer thickness of asphalt pavements affect how they respond to fatigue [22]- [25]. As a result, a thorough performance evaluation of fatigue behaviors takes into account the structural reaction of the entire pavement system.…”
Section: Fig 2 -Cross-section Of Rutting or Permanent Deformation [13]mentioning
confidence: 99%
See 1 more Smart Citation
“…The research has also demonstrated that the stiffness of non-asphalt layers and the layer thickness of asphalt pavements affect how they respond to fatigue [22]- [25]. As a result, a thorough performance evaluation of fatigue behaviors takes into account the structural reaction of the entire pavement system.…”
Section: Fig 2 -Cross-section Of Rutting or Permanent Deformation [13]mentioning
confidence: 99%
“…As a result, a thorough performance evaluation of fatigue behaviors takes into account the structural reaction of the entire pavement system. To identify system features, linear elastic structural response models have been created, such as the WinJULEA platform utilized in the Mechanistic-Empirical Pavement Design Guide (MEPDG) [25]. According to Eslaminia et al [26], current research is going toward linear viscoelastic analysis of multilayer systems since it is thought to be more reflective of pavement response to stress and strain.…”
Section: Fig 2 -Cross-section Of Rutting or Permanent Deformation [13]mentioning
confidence: 99%
“…e viscoplastic Advances in Civil Engineering properties related to the effect of material behaviors were conducted using the constant crosshead test. e background of the theory and experiment for curves are referred in various studies [1,[6][7][8][9][10][11][12][13][14]. e points in this figure indicate the viscoplastic strain rates at the maximum stress in the test applying the strain rate and temperature.…”
Section: Evaluation Of Rutting Performance By Tension Testmentioning
confidence: 99%
“…Different approaches based on newly developed experimental protocols, analytical methods, and/or computational simulations have been employed to advance the prediction of fracture in bituminous materials. Continuum damage modeling is a well‐known approach for evaluating fracture characteristics of bituminous mixtures (Al‐Rub et al., 2012; Daniel & Kim, 2002; Y. R. Kim et al., 2008; Kutay & Lanotte, 2018; Lee et al., 2000; Mensching et al., 2016; Rushing et al., 2017; Underwood et al., 2009; You et al., 2017). In these studies, the researchers have regarded bituminous mixtures as homogenous media, and the evolution of damage due to fatigue cracks has been quantified implicitly based on the overall reduction of material integrity in a homogenized way.…”
Section: Introductionmentioning
confidence: 99%